Therapeutic Effects of Vitamin E in Non-alcoholic Fatty Liver Disease: An Open-Labeled Clinical Trial - Fairooz, Amal jawad; Jamal, Mohammed yawuz; Alkhalidi, Nawal mehdi (Iraqi Journal of Pharmaceutical Sciences, 2022)
Abstract: non-alcoholic fatty liver disease (NAFLD) is one of the widespread chronic liver diseases; it is ranging from simple fat buildup in the liver (steatosis) to non-alcoholic steatohepatitis (NASH) presence of inflammation and hepatocyte injury. This study aims to assess the effect of vitamin E on the degree of fatty infiltration in the liver, liver enzymes, and lipid profile. A prospective open-labeled clinical trial involved (39) Participants diagnosed with NAFLD depending on ultrasonography findings, they were administered vitamin E 800IU\day for 12wks and advised to take low fat, low carbohydrate diet and to do regular sport. Steatosis score, liver enzymes, fasting blood sugar and lipid profile were measured at baseline and repeated at 4wks and 12wks of the study period. Results of this study found that vitamin E reduces steatosis score significantly at 12wks (p=0.0001), while liver enzymes ALT and ALP did not show significant difference throughout the study period at 12wks (p=0.081 for ALT, P=0.117 for ALP) only AST showed significant difference ( p=0.008 at 12wks ), total cholesterol and triglyceride were reduced significantly (p=0.0001 for both) at 4wks and 12wks where HDL and fasting blood glucose were not altered significantly through the study period. In conclusion, vitamin E and lifestyle modifications have a positive impact on patients with NAFLD by reducing steatosis score, lipid profile, and BMI